2020
DOI: 10.1007/s12053-020-09855-7
|View full text |Cite
|
Sign up to set email alerts
|

Are the energy savings of the passive house standard reliable? A review of the as-built thermal and space heating performance of passive house dwellings from 1990 to 2018

Abstract: The Passive House (PH) Standard is a voluntary quality assurance standard focused upon maximising the health and wellbeing of occupants, whilst reducing space heating demand to a very low level. To meet the PH standard well defined criteria have to be met. However, given literature that suggests a 'performance gap' for energy savings, the question remains, how well do PH dwellings perform in situ?This paper presents results from in situ building fabric thermal performance measurements, along with a comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Among the reviewed papers, a few mention only the variable relevant to normalization and not the normalization method [9,11,75,95,106]. Table 2 provides a summary of the most frequently applied methods for normalization and the related normalized variables, together with the respective references.…”
Section: Approaches To Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the reviewed papers, a few mention only the variable relevant to normalization and not the normalization method [9,11,75,95,106]. Table 2 provides a summary of the most frequently applied methods for normalization and the related normalized variables, together with the respective references.…”
Section: Approaches To Normalizationmentioning
confidence: 99%
“…Gas consumption [104] Not specified Space heating [106] Not specified Heating and DHW [9,75] Not specified Final/primary energy use (for heating and DHW) [11,95] Averaging the daily mean power of the heating system when the mean ambient temperature exceeds 23 • C. Mean power was multiplied by the number of hours to obtain DHW heating demand.…”
Section: Approaches To Normalizationmentioning
confidence: 99%
“…For passive houses that were constructed between 1990 and 2018, the building performance that was predicted during the design stage was compared with the actual heating energy consumption, and analyses were performed. The analysis results revealed that OB accounted for a standard deviation of up to 50% [6]. Performing energy retrofitting using OB analysis helps in energy conservation; consequently, it results in excellent building energy performance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of European regulation on energy efficiency and energy conservation, the passive house (PH) concept has emerged as a global quality assurance standard [1][2][3]. Nearly Zero Energy Buildings (NZEBs) have become an essential element in developed countries to achieve a reduction in energy consumption and CO 2 in the construction sector [4][5][6], using efficient systems of HVAC (Heating, Ventilating, and Air-Conditioning) and increasing the thermal insulation of buildings [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main barriers for this type of construction are the high performance building materials and the cost of adoption (training and certification) [9,10]. Some authors stated that a PH should be defined by six principles: (i) a high level of thermal insulation and thermal capacity of opaque walls [3,[5][6][7]11], (ii) minimization of thermal bridges [3,5,11,12], (iii) high efficient windows [5,12], (iv) high levels of airtightness [3,[5][6][7], (v) passive solar gains [7,11,12], and (vi) efficient mechanical ventilation with heat recovery system [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%